(untitled) (mathematica didactica, 2021)
The legitimisation of mathematics education in general education is a central field of study within mathematics education research. Traditionally, the philosophy of mathematics education follows an educational discourse which is shaped by an entanglement of pedagogy and enlightenment. I show which problems arise from a thus conceptualised philosophy of education, which sociologically inspired findings concerning mathematics education may enrich the philosophy of mathematics education and which new problem areas open up as a consequence.